ENT 530 Case Study Company Analysis: Mohd Noor Jaya Enterprise (MN) / Nursalihah Mohamad Dek - Mohamad Dek, Nursalihah (2021)
Mohd Noor Jaya Enterprise was established by a married couple came from Cambodia Mr. Mohd Noor Bin Mohd Sulong and his wife Mrs Rohaya Chin Binti Abdullah. They successful to stay in business clothing industry for ten years which selling Baju Melayu, Kurta and Jubah. Located in Bandar Kota Bharu, the Mohd Noor Jaya store was established in the early 2010 in response to emerging trends and the need for a unique clothing with high quality and low price options. They specialize in the production of clothing and what differentiate them with other existing competitors is that not only producing Baju Melayu with different type, Mohd Noor Jaya has Kurta for mans and kids too with many size option. As the one of bigger clothing wholesaler in Pantai Cahaya Bulan area, Mohd Noor Jaya or MN company able to capture a large share of the market. Located in an owned building with a concept of yellow and green based, Mohd Noor Jaya produce clothing product with high quality fabrics that imported from Japan and Korea. Customer can also buying MN product through postage delivery, pick up at the store and Mohd Noor Jaya Enterprise also grow his business using intermediaries such as agent and dropship. MN company aims to offer its products at a competitive price to meet the demand of the low to middle income local market area people. Their company vision is to fulfil their customers need and want to make them loyal to Mohd Noor Jaya collection. In this report, there are a few problems that MN company faced which cause MN brand to lag behind other brands such as lack of talented employees to produce clothes design that follow current trends because company only hiring cheap employees. The next problem is, MN company have a money management issue because of the owner given the permission to agent borrow the stock without paying in advance. Last is lack of customer awareness because of the owner not updated their marketing tools like Facebook page almost seven months that cause low brand awareness. Based on the major problem, there are the best problem solving that suitable for MN company to follow up for stay as one of the biggest clothing wholesaler at Kota Bharu area. The first solution is, the owner should give requirement to the person that want to be his staff at least have two experience in fashion design. Next is owner should have a financial report to report the profits and losses.